Feasting on foreign aid : a political economic examination of foreign aid's potential role in perpetuating chronic hunger and starvation in Malawi - Knoetze, Christopher (Department of Political Studies, 2016)
Foreign aid to Malawi has the ability to perpetuate the country's fifteen-year long hunger crisis. For millions of Malawians, chronic starvation is attributable to their inability to access food available on internationalised markets. Bilateral foreign aid to the Southern African state is aimed at stimulating development which, if successful, should also lift the country beyond threat of chronic, long-term malnourishment for the poorest of its citizens. Donor's, however, measure developmental aid's success along a narrow set of indicators - such as economic growth - dictating the direction of policy for recipient nations wishing to maintain the inflow of aid. For Malawi, this is all but inevitable as foreign aid accounts for 40% of government revenue. As a result of this dependency on external income, Malawi's government has targeted economic growth in order to maintain its aid support. Economic growth in Malawi has been fuelled by public spending and is unsustainable in the long term. The rapid growth was accompanied by high levels of inflation and the further entrenchment of a perennial trade accounts deficit, leaving the national currency weak. In addition, the majority of public spending reinforces the country's economic identity of an agricultural state, ensuring that 90% of Malawians who rely on agriculture for an income will remain poor due to the imbalance of trade. The indirect perpetuation of an agricultural economy, alongside unsustainable and unstable growth, has led to a situation where most Malawians cannot afford to buy food.